PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN KEPUASAAN KERJA TERHADAP KINERJA KARYAWAN PADA PT ARVENA SEPAKAT KABUPATEN INDRAGIRI HULU - Yani Tri; Ganarsih Lestari Raden; Ningsih Suryati Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this research was to find out the effect of compensation, work environment, and job satisfaction on employee performance at PT Arvena Sepakat Kabupaten Indragiri Hulu. The population were 50 employees with saturation sampling. The data used in this study was primery data and the data analysis was multiple linear regression analysis with employee performance as the dependent variable and three independent variables are compensation, work environment, and job satisfaction. The result of the study found that : 1) Compesation has significant effect on the employee performance 2) Work environment has significant effect on the employee performance 3) Job satisfaction has significant effect on the employee performance.Keyword : Compensation, Work Environment, Job Satisfaction, Employee Performance